Science as Sacred Myth? Ecospirituality in the Anthropocene Age. (30th July 2015) - Sideris, Lisa
Abstract : This article focuses on New Story/Universe Story/Epic of Evolution movements, forms of science-based ecospirituality that have emerged in recent decades. One of my central claims is that these narratives tend to encourage awe and wonder at scientific information and expert knowledge as that which is most 'real', over and above direct encounters with the natural world. As such, I question whether these new myths are likely to engender the environmental values they seek to cultivate. Everyday experiences and encounters with the natural world—encounters not filtered through scientific analysis and explanation—are likely to be devalued in this worldview. This tendency is particularly pronounced in iterations that are inspired by the work of E.O. Wilson and Richard Dawkins, both of whom promote a mythopoeic rendering of scientific information as a robust and superior rival to religion. Espousing a religion based on scientific reality, some proponents of these narratives express attitudes of intolerance toward religious and cultural traditions that do not derive meaning and value directly from science, even though these traditions may embrace green values on their own terms. As a whole these movements discourage sensory, experience-infused forms of engagement with nature that are less dependent upon and mediated by expert knowledge.